Role of nucleation in cortical microtubule array organization: variations on a theme. (1st April 2013) - Fishel, Erica A.; Dixit, Ram
Summary The interphase cortical microtubules (CMTs) of plant cells form strikingly ordered arrays in the absence of a dedicated microtubule‐organizing center. Considerable research effort has focused on activities such as bundling and severing that occur after CMT nucleation and are thought to be important for generating and maintaining ordered arrays. In this review, we focus on how nucleation affects CMT array organization. The bulk of CMTs are initiated from γ–tubulin‐containing nucleation complexes localized to the lateral walls of pre‐existing CMTs. These CMTs grow either at an acute angle or parallel to the pre‐existing CMT. Although the impact of microtubule‐dependent nucleation is not fully understood, recent genetic, live‐cell imaging and computer simulation studies have demonstrated that the location, timing and geometry of CMT nucleation have a considerable impact on the organization and orientation of the CMT array. These nucleation properties are defined by the composition, position and dynamics of γ–tubulin‐containing nucleation complexes, which represent control points for the cell to regulate CMT array organization.